Hybrid gel with metallic inclusion - Tan, Ting Xian. (2012)
The presence of symmetric dilatation in single spherical hydrogels or biogels often occurs due to minimal changes in its environment conditions. This causes unnecessary stress and forces acting on the material itself. The situation of the material itself now changes from a single phase consistent material to two layered spherical hybrid gel with a combination of a metallic material inclusion. With the metallic inclusion, the stresses induced to the sphere changes and vary through the two layered sphere itself.